Uma proposta didática para o ensino de MMC e MDC no ensino médio - Mariano, Jegiane Carla Favoreto (2024)
This work consists of a didactic sequence aimed at first-year high school students, with the purpose of consolidating the learning of the Greatest Common Divisor (GCD) and the Least Common Multiple (LCM), topics previously covered in elementary school that are essential for the introduction of new content. This sequence, based on problem-solving, aims to review GCD and LCM and also to expand knowledge on topics related to these subjects that are not always addressed in basic education, such as Euclid's Algorithm and the Chinese Remainder Theorem. To achieve these objectives, the approach to these contents in two Mathematics textbooks used in elementary school is analyzed, and a diagnostic assessment is applied to two first-year high school classes at EEEM Arnulpho Mattos, in the city of Vitória (ES), aiming to determine the students' prior knowledge of the topics under study. Based on this, review classes were planned and a final assessment was applied to determine the knowledge acquired by the students after the review. Finally, the data collected from both assessments were analyzed to verify the students' progress and the effectiveness of the didactic sequence